2021
DOI: 10.1186/s11689-021-09403-z
|View full text |Cite|
|
Sign up to set email alerts
|

Pleiotropy between language impairment and broader behavioral disorders—an investigation of both common and rare genetic variants

Abstract: Background Language plays a major role in human behavior. For this reason, neurodevelopmental and psychiatric disorders in which linguistic ability is impaired could have a big impact on the individual’s social interaction and general wellbeing. Such disorders tend to have a strong genetic component, but most past studies examined mostly the linguistic overlaps across these disorders; investigations into their genetic overlaps are limited. The aim of this study was to assess the potential genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 119 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…Language plays a major part in the outcomes of ASD. ASD children whose language is impaired, could have a large impact on the social interaction and general wellbeing of individuals (Nudel et al, 2021). Improvements in the language of ASD children before 5 years old may result in catching up to overall average levels in developmental trajectories, whereas the remainders may develop ID (Pickles et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Language plays a major part in the outcomes of ASD. ASD children whose language is impaired, could have a large impact on the social interaction and general wellbeing of individuals (Nudel et al, 2021). Improvements in the language of ASD children before 5 years old may result in catching up to overall average levels in developmental trajectories, whereas the remainders may develop ID (Pickles et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, children with lower language competence had a greater chance of finding genetic variants. Nudel et al (2021) considered it as pleiotropy between language impairment and ASD. They observed a significant genetic overlap between specific language impairment and childhood autism (which excluded Asperger's syndrome).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that there may be multiple risk factors, which can reinforce each other, like chronic otitis media ( 5 ), socio-economic status ( 6 ), and oral-motor difficulties ( 7 ). As stated above, it is well known that language problems can co-occur with autism spectrum disorder ( 8 ), behavioral disorders ( 9 ) and certain epilepsy disorders ( 10 ). Furthermore, family and twin studies have indicated that DLD have a strong genetic component ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, disentangling the polygenic contribution in DLD is lagging compared to the monogenic forms. Few studies investigated the polygenic overlap between DLD and other NDD without identifying any major signi cant association (Dale et al, 2020;Nudel et al, 2021). A recent genome-wide association study (GWAS) identi ed a robust single nucleotide polymorphism (SNP) heritability of ve reading-and/or language-related traits, not including DLD, that explained 13-26% of traits variability (Eising et al, 2022).…”
Section: Introductionmentioning
confidence: 99%